P49. Prognostic value of muscle ultrasound in the D50 progression model of amyotrophic lateral sclerosis. Issue 8 (August 2018) - Heiling, B.; Ceanga, M.; Fedtke, N.; Stubendorff, B.; Grimm, A.; Rödiger, A.; Axer, H.; Witte, O.W.; Grosskreutz, J.
Abstract : Background: The diagnostic value of muscle ultrasound in the diagnosis of amyotrophic lateral sclerosis (ALS) has increased because it can detect fasciculations more reliably than EMG in certain muscle groups (e.g. tongue) as well as it can access certain muscle groups more easily than EMG (e.g. tongue, diaphragm, abdominal muscles). Recently, we have introduced the D50 ALS model which enables the assessment and the comparison of individual ALS disease courses. In this retrospective study we aim to explore the role of muscle ultrasound in clinical routine in relation to ALS progression parameters in a large cohort. Methods: 4 year ultrasonography data (echo intensity and fasciculation) in 6 muscle groups of 220 ALS patients were related to the onset type, disease duration, ALSFRS-R, its progression rate, D50 (= time [months] taken for ALSFRS-R to drop to 24) and relative D50 (rD50 = calculated value describing individual disease covered in reference to D50). In a patient subset of 23 patients repeated measurements during disease progression were performed to monitor both clinical an ultrasonographic changes over time. Results: We observed significant differences in echo intensity between slow (D50 > 40 months) and fast (D50 < 20 months) progressive ALS patients and an increase in echo intensity between disease phase I and phase II. Furthermore, we detected a tendency towards a higher Heckmatt Score already in disease phase I in patients with a more aggressive disease course. Conclusion: Muscle ultrasound has an important diagnostic value in early ALS. Combined with the D50 model of ALS progression, it can aid prognostic stratification which is important for patients planning, inclusion into future clinical trials and the understanding of the underlying pathology. Acknowledgements: We thank Mandy Arnold and Cindy Höpfner for her excellent patient care and clinical data collection. This study was supported by grants to JG by theBMBF through the E-RARE framework (PYRAMID) andJPND (OnWebDuals) and in collaboration with theGerman Network for Motoneuron Diseases (MND-NET).